Model of Formation of Deviantological Competence of the Teacher - Mukhtarova, Shakira; Michvocíková , Veronika; Baimukanova , Marzhangul; Barikova , Alyona (Pedagogy and Psychology, 2025)
The study examines the problem of developing teachers’ deviantological competence. The relevance of the problem is dictated by the current situation and is associated with the growth of deviant manifestations in the behavior of adolescents. Methodology and Methods. On the basis of a system-activity and competence approach, a model of deviantological competence was developed and a diagnosis of the current level of development of the professional readiness of teachers to interact with children of deviant behavior was carried out. The research methods included analysis, synthesis, modeling, and a questionnaire survey. Results. The study identified the actual level of teachers’ readiness to work with children with deviant behavior: most respondents demonstrated only general knowledge and understanding, while only a small proportion possessed specific professional knowledge and skills in this area. Scientific Novelty. The concept of «teachers’ deviantological competence» is defined, its correlation with the concept of «teachers’ professional readiness to interact with children with deviant behavior» is demonstrated, the components of the studied phenomenon are determined, and a structural model is presented. Practical Significance. The findings reveal the need for teachers’ professional development to provide effective socio-pedagogical support to children with deviant behavior.